Utilization of Elastomeric Materials in the Conditions of Experimental Production - Oleksandr Dobrodomov; Yurii Tkachov (Challenges and Issues of Modern Science)
Efficient cost reduction in experimental production requires a comprehensive approach and consideration of specific conditions and possibilities of the enterprise. Automation, robotization, the use of universal numerically controlled machines, and the implementation of other advanced technologies in the context of the mentioned production can result in significant initial investments and a substantial increase in product costs in the early stages. However, in the long-term perspective, such an approach undoubtedly leads to a decrease in overall expenses. Despite its advantages, at the early stages of innovative projects, particularly in the field of mechanical engineering, costs associated with increased fixed assets are practically unacceptable due to the lack of financial resources. Experimental production exhibits all the characteristics of a single-unit production. If we open any textbook on mechanical engineering technology, we can read something like this: the main features of single-unit production include a low probability of product repetition, the use of versatile equipment, and highly skilled workers. It is clear that the higher the level of automation, the greater the initial capital investments, but the lower the labor costs due to a reduction in the number of production personnel.